Libido disorders in men in borderline mental disorders - M. I. Yagubov; I. Yu. Kan (Лечащий Врач)
The article offers diagnostic and therapeutic programs for examining and treatment of male patients suffering from libido disorders, which are more often caused by borderline mental disorders. A description of comprehensive diagnosis of these disorders is given, as well as clinical variants of their course, principles and tactics of treatment and rehabilitation measures, taking into account the structure of mental and sexual pathology. Particular attention is paid to the differential diagnosis of sexual desire disorders in the framework of various mental disorders.